Conversion from insulin glargine U-100 to insulin glargine U-300 or insulin degludec and the impact on dosage requirements. (April 2018) - Pearson, Scott M.; Trujillo, Jennifer M.
Background: We wanted to determine whether basal insulin requirements change when patients transition from insulin glargine U-100 (Gla-100) to insulin glargine U-300 (Gla-300) or insulin degludec. Methods: This study involved subjects seen in the University of Colorado Health Endocrine Clinic who were transitioned from Gla-100 to either Gla-300 ( n = 95) or insulin degludec ( n = 39). The primary outcome was the difference between baseline Gla-100 dose and dose of Gla-300 or insulin degludec prescribed after first follow-up visit within 1–12 months. Secondary outcomes included changes in glycemic control and empiric dose conversion from Gla-100 to Gla-300 or insulin degludec on the day of transition. Wilcoxon rank sum tests evaluated changes in insulin doses, and paired t tests assessed changes in glycemic control using GraphPad statistical software. Results: Median daily basal insulin dose increased for individuals transitioned from Gla-100 to Gla-300 from 30 [19–60 interquartile range (IQR)] units at baseline to 34.5 (19–70 IQR) units after follow up ( p = 0.01). For patients transitioned to insulin degludec, dose changes from baseline to follow up were not significantly different ( p = 0.56). At the time of transition, the prescribed dose of Gla-300 or insulin degludec did not significantly differ from the previous dose of Gla-100 ( p = 0.73 and 0.28, respectively), indicating that empiric dose adjustments were not routinely prescribed. Conclusions: Patients who transitioned from Gla-100 to Gla-300 had increased basal insulin requirements between visits, while basal insulin requirements for those transitioned from Gla-100 to insulin degludec were not significantly different.